The Curriculum-Based Strategies for Strengthening Social Analysis Skills among Tafsir Students - Nur Rofiah; Iwan Satiri; Ahmad Juraidi; Salman Faris; Ahmad Zulki; Tri Kurnia Revul Andina (ZAD Al-Mufassirin, 2026)
Research conducted by tafsir students on social problems requires strong social analysis skills in order to trace the roots of injustice and ensure that the resulting Qur’anic exegesis is appropriately directed. This study aimed to identify curriculum-based strategies for strengthening the social analysis skills of tafsir students. It employed a qualitative approach based on library research. Relevant literature was analyzed using the theory of the integration of general and religious sciences in order to demonstrate the importance of integrating tafsir studies with the social sciences and to formulate strategies for strengthening students’ social analysis through the curriculum. The study identified four curriculum-based strategies for strengthening social analysis: an embedded approach, namely inserting social analysis into existing courses; a parallel approach, namely offering a specific course on social analysis; an extracurricular approach, namely organizing social analysis training; and a transdisciplinary approach, namely enabling students to take relevant courses in other faculties or universities. The findings affirm the urgency of integrating tafsir studies with the social sciences and offer four alternative strategies that may be useful for heads of Qur’anic and Tafsir Studies programs in strengthening students’ social analysis skills.